Flash Sales and FOMO : Evidence from Gadget Impulse Buying - Agrawal, Shraddha; Kaur, Gurpreet; Mittal, Arjun (Indian Journal of Marketing, 2026)
Purpose : The research focused on understanding the impact of flash sales on impulse buying behavior in the gadget industry. It also explored the effect of fear of missing out (FOMO) on the sales of the gadgets. Design/Methodology/Approach : The research employed a quantitative method, and the primary data were collected through a structured questionnaire. The sample size was 340 Indian consumers who had engaged in impulse purchases of electronic items. To gather constructive insights, purposive sampling was used. Data analysis was conducted with the help of PLS-SEM. Results : The results of the study revealed a positive correlation between flash sales and impulse buying. The impact of fear of missing out (FOMO) was a partial mediation effect on the relationship. This proved that the psychological pressure often triggered impulsive purchases among consumers, and their decisions were more driven by promotional triggers. It was also shown that with increasing age and income, there was less impact of these strategies and marketing techniques. However, the flash sales worked best on the younger generations due to their interest in technology. Practical Implications : The results provided actionable recommendations for digital retailers and marketers regarding flash sales, even for high-involvement products like gadgets. Additionally, the results highlighted the need for ethical promotion design, especially when dealing with younger and more vulnerable consumers. Originality/Value : The study built upon the literature of impulse buying by contributing to the understanding of emotionally driven decision-making in digital markets by empirically exploring the FOMO as a mediating variable in the purchase of gadgets in flash sales.